Analisis Manajemen Risiko Usaha Konveksi Menggunakan Pendekatan ISO 31000 - Almaira Sarah Junjunan; Nisa Febrianti; Muhammad Shoffan Anbiya; Sarah Mutia Azahra; Alfiana Alfiana (Indo Publishing, 2026)
This study examines risk management practices in a small-scale garment business, Planet Lain Konveksi, located in Bandung City. Small and medium-sized enterprises in the garment sector face various uncertainties that may disrupt production activities and affect business sustainability. This research aims to identify potential risks encountered by the business and to analyze the application of risk management based on the ISO 31000 framework. A qualitative descriptive approach was employed using direct observation and interviews with the business owner as the primary data sources. The results indicate that Planet Lain Konveksi is exposed to several key risks, including operational, financial, human resource, marketing, market, and legal risks. Some risks demonstrate relatively high levels of impact and likelihood, particularly those related to raw material delays, machine breakdowns, and delayed customer payments. The implementation of ISO 31000-based risk management is expected to support SMEs in anticipating potential issues, improving operational stability, and maintaining business sustainability within the increasingly competitive garment industry.